A novel anti-HER2 monoclonal antibody IAH0968 in HER2-positive heavily pretreated solid tumors: results from a phase Ia/Ib first-in-human, open-label, single center study - Song, Na; Teng, Yuee; Shi, Jing; Teng, Zan; Jin, Bo; Qu, Jinglei; Zhang, Lingyun; Yu, Ping; Zhao, Lei; Wang, Jin; Li, Aodi; Tong, Linlin; et al. (Frontiers in Immunology, 2024)
Background: IAH0968 is an afucosylated anti-epidermal growth factor receptor 2 (HER2) monoclonal antibody which improved the activity of antibody-dependent cellular cytotoxicity (ADCC) and superior anti-tumor efficacy.To determine the maximum tolerated dose (MTD) with dose-limiting toxicity (DLT), a single institution, phase Ia/Ib study was undertaken, using 3 + 3 design. The primary endpoints were safety, tolerability and preliminary clinical activity. Eighteen patients were evaluable for safety and fifteen patients were suitable for efficacy analysis. Dose escalations were 6 mg/kg (N = 2), 10 mg/kg (N = 7), 15 mg/kg (N = 5), and tolerable up to 20 mg/kg (N = 4).Results: Only one DLT was found at dosage 10 mg/kg, and no MTD was reached. The most common Grade 3 treatment-related adverse events (TRAEs) were hypokalemia (5.6%), supraventricular tachycardia (5.6%), interval extension of QTC (5.6%), and infusion reaction (5.6%). Grade 4 TRAE was arrhythmia (5.6%). No serious TRAE or Grade 5 was reported. 22.2% of patients had a TRAE leading to dose adjustment and 16.7% of patients had a TRAE resulting in discontinuation of IAH0968. After a median follow-up of 9.7 months (range, 3.7 -22.0), the objective response rate (ORR) was 13.3% (2/15), the disease control rate (DCR) was 53.3% (8/15), and median progression-free survival (mPFS) was 4.2 months (95% CI: 1.4 -7.7), and the median duration of disease control (DDC) was 6.3 months (95% CI: 2.9-not reached), with 4/15 responses ongoing. Conclusions: In HER2-positive heavily pretreated metastatic patients, IAH0968 demonstrated promising clinical activity with durable responses and tolerable safety profiles.